KOPING PERAWAT TERHADAP STRESS KERJA DI RUANG RAWAT INAP BOUGENVILE RUMAH SAKIT TELOGOREJO SEMARANG TAHUN 2OO4 - M Fatkhul Mubin; I 'ien Noer Aini (JURNAL LITBANG, 2005)
Abstract Stress is typical correlation between individual and his environment so it endangers his Prosperity. Sources of stress (stressor) are an occurrence, situation, project or individual able to cause stress. Stressor can come from one who hit by stress (internal resources) or from outside (external sources) both on environment and family. Nurses work fully responsibility to people safety so this work can become stressor Researched by Grawt and friends (1989) in English concerning stressor in nurse treatment worked in many different field determine that 67%o Respondents expressed the ratio between service and source had unbalanced, 34?6 express work Finishing deadline determined by others and not himself. So it needed soul (coping) defense mechanism, as problem preventive process at individual to manage the stress condition. This research aims to know nurse was coping used in overcoming the effect of their work Nurse's perception about work stress and this study also identified nurse's way overcoming stress Emerging in her work. Cross sectional study using survey method was applied in this study, with aims to know nurse coping to work stress in Bougainville room Tlogorejo Hospital Semarang. The nurse Research subject counted 67 people with taken sample was to represent each floor at Bougainville room taken by random proportional depend on the amount of nurse percentage each floor The Bougainville Room consist of 4 floor The Reach result indicates .that : a. At nurse frequency distribution depend on perception of work stressor could be known that most nurse 6 7 (9 7 %o) expressing low s tress or. b. At nurse distribution depend on coping focusing at problem could be identified most responder have coping depend on positive trouble solving 100%. c. At Nurse distribution depend on emotion arrangement coping could be described that the most responder have coping de end on positive emotion arrangement ( I 0 0%o). Suggestion given (a) a requirement to improve good employees between colleague and other health team, (b) require to improve treatment ability both skill and or, knowledge, (c) Establishment conducive work environment, (d) evaluate and follow-up if there is problem of nurse. Key word: stress, nurse, coping